Prevalence of Delayed Initiation of Breastfeeding and Its Associated Factors Among Mothers Who Gave Birth by Cesarean Section in Gamo and Gofa Zones, Southern Ethiopia: A Multicenter Cross-Sectional Study - Arega Abebe Lonsako; Tsehaynew Kasse; Aster Dure; Abera Cheru; Kinde Kibe; Addisalem Haile (Journal of Nutrition and Metabolism)
Conclusions: This study found a high prevalence of delayed breastfeeding initiation among mothers who had cesarean sections, with significant factors including primiparity, a lack of professional assistance, the absence of early skin-to-skin contact, and inadequate postcesarean counseling. To address this, targeted interventions are essential, including enhancing antenatal care services, providing comprehensive breastfeeding counseling, promoting immediate skin-to-skin contact, and ensuring professional support for mothers postdelivery.